2008
DOI: 10.1111/j.1755-263x.2008.00008_1.x
|View full text |Cite
|
Sign up to set email alerts
|

Conservation action in a changing climate

Abstract: Climate change will pose new challenges to conserving Earth's natural ecosystems, due to incremental changes in temperature and weather patterns, and to increased frequency and intensity of extreme climate events. Addressing these challenges will require pragmatic conservation actions informed by sitespecific understanding of susceptibility to climate change and capacity of societies to cope with and adapt to change. Depending on a location's environmental susceptibility and social adaptive capacity, appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
209
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(211 citation statements)
references
References 31 publications
0
209
0
2
Order By: Relevance
“…Bleaching occurred across many WIO reefs during 1998, with coral mortality from 1 to 95 per cent depending on local conditions McClanahan et al 2008). Fish-community effects were apparent throughout the WIO but were patchily distributed, reflecting the dependencies of individual species on corals.…”
Section: Introductionmentioning
confidence: 99%
“…Bleaching occurred across many WIO reefs during 1998, with coral mortality from 1 to 95 per cent depending on local conditions McClanahan et al 2008). Fish-community effects were apparent throughout the WIO but were patchily distributed, reflecting the dependencies of individual species on corals.…”
Section: Introductionmentioning
confidence: 99%
“…In Australia, Marshall (2007) found that perceptions of policies could significantly impact on the capacity of commercial fishers to cope and adapt to policy implementation. In general, MPAs that are implemented without due consideration of the likely social consequences can be associated with poor compliance (Sutinen and Kuperan 1999;Christie et al 2003;McClanahan et al 2008). This, in turn, compromises the ability of the MPA to deliver both conservation outcomes and long-term social and economic benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional practices of conserving and restoring biodiversity by direct appeal to historical conditions are being reconsidered in the light of rapid environmental change (Seastadt, Hobbs, & Suding, 2008;Choi et al, 2008;McClanahan, 2008). For a species to survive the projected climate change in their current ranges they must tolerate the new conditions, or successfully colonize new areas with suitable conditions.…”
Section: The Role Of Managed Migrationmentioning
confidence: 99%